Very late recurrence of iris melanoma: 45 years after treatment. Issue 3 (June 2020) - Bosello, Francesca; Al-Jamal, Rana'a T.; Cohen, Victoria M.L.
Abstract : Iris melanoma is a rare tumour that accounts for ~3–4% of all uveal melanoma cases. In the past, surgical resection was the sole treatement option, whereas nowadays, it has been replaced by brachytherapy as treatment of choice. Surgical resection is still in use in selected cases but combined with adjuvant radiotherapy in cases of incomplete resection. Herein, we report the case of a very late recurrence, 45 years after surgical resection. A literature review was performed to detect the latest recurrence reported to date and to understand the etiology behind very late recurrences. The role of multiple factors is discussed to explain this extremely delayed growth.